Design, simulation and fabrication of silicon carbide metal semiconductor field effect transistors - Zhu, Chunlin (2008)
SiC MESFETs have been designed, simulated, fabricated and characterized for high power, high frequency and high temperature applications due to the excellent electronic and physical properties of SiC, such as wide band gap, high breakdown electric field strength, large electron saturation velocity and high thermal conductivity.